Restoring GABAB receptor expression in the ventral tegmental area of methamphetamine addicted mice inhibits locomotor sensitization and drug seeking behavior - Hleihil, Mohammad; Benke, Dietmar (Frontiers in Molecular Neuroscience, 2024)
Repeated exposure to psychostimulants such as methamphetamine (METH) induces neuronal adaptations in the mesocorticolimbic dopamine system, including the ventral tegmental area (VTA). These changes lead to persistently enhanced neuronal activity causing increased dopamine release and addictive phenotypes. A factor contributing to increased dopaminergic activity in this system appears to be reduced GABAB receptor-mediated neuronal inhibition in the VTA. Dephosphorylation of serine 783 (Ser783) of the GABAB2 subunit by protein phosphatase 2A (PP2A) appears to trigger the downregulation GABAB receptors in psychostimulant-addicted rodents. Therefore, preventing the interaction of GABAB receptors with PP2A using an interfering peptide is a promising strategy to restore GABAB receptor-mediated neuronal inhibition. We have previously developed an interfering peptide (PP2A-Pep) that inhibits the GABAB receptors/PP2A interaction and thereby restores receptor expression under pathological conditions. Here, we tested the hypothesis that restoration of GABAB receptor expression in the VTA of METH addicted mice reduce addictive phenotypes. We found that the expression of GABAB receptors was significantly reduced in the VTA and nucleus accumbens but not in the hippocampus and somatosensory cortex of METH-addicted mice. Infusion of PP2A-Pep into the VTA of METH-addicted mice restored GABAB receptor expression in the VTA and inhibited METH-induced locomotor sensitization as assessed in the open field test. Moreover, administration of PP2A-Pep into the VTA also reduced drug seeking behavior in the conditioned place preference test. These observations underscore the importance of VTA GABAB receptors in controlling addictive phenotypes. Furthermore, this study illustrates the value of interfering peptides targeting diseases-related protein-protein interactions as an alternative approach for a potential development of selective therapeutic interventions.